How outward foreign direct investment can drive a nation towards a more productive country / Suhailee Aminuddin and Kama Khairil Anuar Yusof - Aminuddin, Suhailee; Yusof, Kama Khairil Anuar (2014)
Malaysia has become an important source of foreign direct investment in Southeast Asia. Foreign direct investment is one way to measure the performance of developing countries. Besides, it may contribute to positive economic growth and also stability of economy in countries. This research will discuss on how outward foreign direct investment can drive nation towards a more productive country. A few factors may influence outward foreign direct investment in Malaysia. Hence, this study is designed to examine the factors that more significant that influence outward foreign direct investment. Outward foreign direct investment as dependent variable and five variables which is unemployment rate, effective interest rate, country productivity, gross domestic product and exchange rate as the independent variables. This research based on the data collected from 1983 until 2012. Several suggestions also will be discussed at the end of this study.